Pengaruh Kecerdasan Emosional dan Iklim Organisasi terhadap Kepuasan Kerja Dosen Politeknik Negeri Jakarta - Narulita Syarweny (Research Center and Case Clearing House PPM School of Management, 2023)
The purpose of this study was to analyze the effect of both individually and collectively on emotional intelligence and organizational climate on the job satisfaction of lecturers at the Jakarta State Polytechnic. In this research, the method used is a survei method with a quantitative research approach using path analysis techniques. The population is all lecturers at the Jakarta State Polytechnic (325 people); using the Slovin formula, a sample of 77 people is obtained. This path analysis examines the effect of emotional intelligence using self-awareness, self-regulation, motivation, empathy, and social skills, and organizational climate using job situation and task, responsibility, identity, warmth, support, and conflict indicators on job satisfaction. With indicators of compensation, the work itself, promotion, and supervision, the result is that the emotional intelligence of lecturers influences the increased job satisfaction of lecturers; increasing job satisfaction is due to the increasing organizational climate at the Jakarta State Polytechnic and the simultaneous increase in Emotional Intelligence and Organizational Climate causes Job satisfaction of Jakarta State Polytechnic lecturers.